THE PREVALENCE OF SYMPTOMS OF ALLERGIC DISEASESIN CHILDREN RESIDING IN INDUSTRIALREGIONS OF UZBEKISTAN - ChoiA, Jae Wook (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to such an urgent problem of social medicine as asthma and allergies in children, which has important theoretical and practical significance. The article is based on the results of epidemiological studies performed by a team of authors. The paper summarizes and highlights internationally recognized methods for studying the true prevalence of diseases among the population through questionnaires. Among the modern problems of medicine and health care that attract the attention of researchers around the world, an important place is occupied by allergic diseases: bronchial asthma, allergic rhinitis and atopic dermatitis. The researchers found that the presence of a hereditary predisposition to allergic diseases in the family is a significant risk factor. At the same time, environmental factors also remain important factors in the occurrence and exacerbation of allergic diseases. The study, in which visits to the hospital of children with repeated exacerbations of allergic diseases were analyzed, indicates that industrial air pollution, especially near the house where the child lives, affects the clinical manifestations and the severity of the disease. Evaluation of the role of adverse effects on the human body due to environmental pollution is the most important task of medicine and is of great medical and social importance. This task is of particular importance for pediatrics, dealing with a growing organism that is sensitive to any environmental influences.